Multispecialty Intraoperative Approach for Treatment of Intra-Articular Knee Venous Malformations. Issue 3 (September 2021) - Kini, Sameer; Desai, Sudhen B.; Chau, Alex; Kukreja, Kamlesh U.; Kan, J. Herman; McKay, Scott D.
Abstract : Intra-articular venous malformations (IAVMs) pose a treatment dilemma for a variety of specialties. Here, we discuss a multispecialty approach between orthopedic surgery and interventional radiology to treat pediatric knee IAVMs in a 4 patient case series. The technique involved the use of arthroscopy along with ultrasonography for direct visualization of the lesions for the purpose of sclerotherapy. The combined approach with both radiologic imaging and arthroscopic techniques provided the opportunity for diagnosis and therapeutic intervention in a single procedure. In our patient series, we noted significant qualitative improvement in symptoms and patient function with minimal complications. This multispecialty approach provides an efficient management strategy for pediatric knee IAVMs.